Investigation of genetic diversity in Russian collections of raspberry and blue honeysuckle - Lamoureux, D.; Sorokin, A.; Lefevre, I.; Alexanian, S.; Eyzaguirre, Pablo B.; Hausman, J. (Cambridge University Press, 2011)
The N.I. Vavilov Institute of Plant Industry (VIR) holds and maintains collections of various crop plants among the largest and oldest worldwide. Among them, small berry trees have gained attention because of their potential for human health. Small berries, usually containing various valuable compounds such as vitamins or antioxidants in significant quantities, could be used for easily improving the human diet. Subsets of VIR collections of raspberry (Rubus idaeus L.) and blue honeysuckle (Lonicera caerulea L.) were investigated for genetic diversity. Ninety-five raspberry accessions were genotyped with eight nuclear simple-sequence repeat (microsatellite) markers. Results indicated a fair level of genetic diversity, but also a structure of three main groups in the collection. Blue honeysuckle accessions were genotyped with five intersimple-sequence repeat markers, yielding more than 1100 polymorphic fragments across the 194 accessions. Statistical analysis of these data showed that the subspecies level was key in explaining blue honeysuckle diversity. This study shows that the collections constitute important resources that could be used for either direct consumption goals or breeding of new cultivars. Results may also be used to establish recommendations for efficient conservation of these genetic resources.